PELAYANAN SEKTOR PUBLIK OLEH PEMERINTAH KOTA PEKANBARU TERKAIT PENYAMPAIAN ASPIRASI MASYARAKAT MELALUI APLIKASI LAPOR! TAHUN 2019 - Inka Shinta; Zulfa Harirah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Based on Presidential Regulation Number 76 of 2013 concerning Management of Public Service Complaints, a Service Complaint Management System is established National Public Service for People’s Aspirations and Online (SP4N-LAPOR!). In 2016 the Pekanbaru City Government participated in implementing the LAPOR! by forming a coordinating team for complaint management and officers LAPOR! management administrator! SP4N Pekanbaru City Government. In implementation has resulted in problems, namely the lack OPD response in respond to complaints that come in through LAPOR! and there are still people who do not understand the use of LAPOR!. The purpose of this research namely to find out public sector services by the Pekanbaru City Government related to conveying public aspirations through the LAPOR! year 2019. Theory used in this study is the theory of public service quality proposed by Zeithahaml, Parasuraman & Berry. This research uses qualitative method with a descriptive approach. Data collection techniques with interviews and documentation. Based on the results of the study, it can be concluded that public sector services by the Pekanbaru City Government are related to the delivery of people’s aspirations through the LAPOR! in 2019 everything is going well except for physical evidence indicators which still need to be improved, especially in terms of communication media. And then on the action response indicator Further, the settlement of complaints in Pekanbaru City from the public is still not good because from the example that the researcher described above, there is still a delay in the response from Relevant OPD who still have not followed up on complaints. Keywords: Public Service, LAPOR! (Aspirations and Complaints Service People’s Online)